Phonon Analysis of 2D Organic‐Halide Perovskites in the Low‐ and Mid‐IR Region. Issue 16 (16th June 2022) - Chen, Yan‐Fang; Mahata, Arup; Lubio, Aura D.; Cinquino, Marco; Coriolano, Annalisa; Skokan, Lilian; Jeong, Young‐Gyun; Razzari, Luca; De Marco, Luisa; Ruediger, Andreas; De Angelis, Filippo; Colella, Silvia; et al.
Abstract: Combining the characteristics of hybrid perovskites and layered materials, 2D Ruddlesden–Popper perovskites exhibit unique properties, some of which still require to be deeply understood. In this study, the vibrational signatures of such materials are analyzed by collecting experimental Raman spectra of four distinct compounds. Supported by density functional theory simulations, the role of the phenyl spacer single fluorination on the phonon modes of two similar yet different compounds, i.e., phenethylammonium lead iodide (PEAI) and 4‐fluorophenethylammonium lead iodide (PEAI‐F), is explained. In addition, this work analyzes some so‐far unreported experimental Raman peaks in the 600–1100 cm −1 range and discusses their origin in this class of 2D compounds. This work paves the way for a better design of novel compounds as well as for their exploitation in (opto)electronic applications. Abstract : The vibrational signatures of four different 2D Ruddlesden–Popper perovskites are analyzed by collecting experimental Raman spectra. So‐far unreported experimental Raman peaks in the 600–1100 cm −1 range are found and discussed. This work paves the way for a better design of novel compounds as well as for their exploitation in (opto)electronic applications.